2019
DOI: 10.1080/15389588.2019.1581925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of traffic calming measures on vehicle speeds and pedestrian injury severity in Ghana

Abstract: Objectives: Each year, pedestrian injuries constitute over 40% of all road casualty deaths and up to 60% of all urban road casualty deaths in Ghana. This is as a result of the overwhelming dependence on walking as a mode of transport in an environment where there is high vehicular speeds, and inadequate pedestrian facilities. The objectives of this research were to establish (1) the impact of traffic calming measures on vehicle speeds and (2) the association between traffic calming measures and pedestrians' in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 20 publications
0
30
1
2
Order By: Relevance
“…Legal blood alcohol limits for pedestrians will never be an issue, so preventive measures should aim at protecting these vulnerable road users from harmful impact. Speed control by building speed bumps and speed tables (Bishai and Hyder 2006;Damsere-Derry et al 2019) is shown to be very cost-effective, as well as increased law enforcement (Bishai et al 2008). Safer road crossings where vehicles are forced by physical interventions to lower their speed, are vital for pedestrian safety especially when pedestrians are intoxicated or behave irresponsibly (Gårder 2018).…”
Section: Prevalence (95% Ci)mentioning
confidence: 99%
“…Legal blood alcohol limits for pedestrians will never be an issue, so preventive measures should aim at protecting these vulnerable road users from harmful impact. Speed control by building speed bumps and speed tables (Bishai and Hyder 2006;Damsere-Derry et al 2019) is shown to be very cost-effective, as well as increased law enforcement (Bishai et al 2008). Safer road crossings where vehicles are forced by physical interventions to lower their speed, are vital for pedestrian safety especially when pedestrians are intoxicated or behave irresponsibly (Gårder 2018).…”
Section: Prevalence (95% Ci)mentioning
confidence: 99%
“…Thus, the importance of the environment and infrastructure measures and the need to implement road safety measures integrating the protection of vulnerable road users such as pedestrians have also been highlighted by many other authors [ 8 , 10 , 16 ]. As such, the implementation of road infrastructure measures has proven to be effective in reducing deaths among pedestrians [ 17 ] and is recommended by the World Health Organization [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Controlling speed remains a priority for government, police, and community groups across the world. Evaluating the consequences of speed as well as the effectiveness of interventions aimed at reducing speed have been topics of much empirical interest (e.g., Aarts & van Schagen, 2006; Armour, 1986; Blais & Dupont, 2005; Carr et al., 1980; Chen et al., 2002; Damsere‐Derry et al., 2019; Elvik, 2001; Farmer, 2017; Farmer et al., 1999; Friedman et al., 2009; Gehlert et al., 2012; Holland & Conner, 1996; Joksch, 1993; Kaplan et al., 2000; Mashhadi et al., 2017; Patterson et al., 2002; Ravani & Wang, 2018; Redelmeier et al., 2003; Richter et al., 2006; Roqué & Roberts, 1989; Shinar & Stiebel, 1986; Stanojević et al., 2018; Tester et al., 2004). The present research contributes to the policing and accident prevention literatures by evaluating the effects of an inanimate but realistic‐appearing police cut‐out on motorist behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Given their salience and relevance to both public health and public concern, it is not surprising that a substantial body of research has dedicated itself to understanding traffic collisions and their causes and correlates (e.g., Aarts & van Schagen, 2006; Blincoe, Miller, Zaloshnja, & Lawrence, 2015; Blows, Ameratunga, Ivers, Lo, & Norton, 2005; Joksch, 1993; Mashhadi, Saha, & Ksaibati, 2017; Prati, Puchades, De Angelis, Fraboni, & Pietrantoni, 2018; Richter, Berman, Friedman, & Ben‐David, 2006; Rolison, Regev, Moutari, & Feeney, 2018). It is also not surprising that reducing traffic collisions via intervention programs remains a priority for groups across the world and that testing the effects of such programs remains a focal area of empirical scholarship (e.g., Armour, 1986; Blais & Dupont, 2005; Carr, Schnelle, & Kirchner, 1980; Chen, Meckle, & Wilson, 2002; Clary, 2018; Damsere‐Derry et al., 2019; Elvik, 2001; Gehlert, Schulze, & Schlag, 2012; Holland & Conner, 1996; Kaplan et al., 2000; Mashhadi et al., 2017; Ravani & Wang, 2018; Redelmeier, Tibshirani, & Evans, 2003; Roqué & Roberts, 1989; Shinar & Stiebel, 1986; Stanojević, Sullman, Jovanović, & Stanojević, 2018; Tester, Rutherford, Wald, & Rutherford, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation